HUKUM ONANI: PERSPEKTIF PERBANDINGAN MADZHAB - Ali Trigiyatno (Jurnal Hukum Islam, 2013)
Among the problems often experienced by teenagers and youth is a problem of sexual tension that plagues the times before marriage. One of the 'solutions' taken to relieve it This sexual tension is the practice of masturbation or masturbation It is often done especially by teenage boys than girls. Most scholars have declared this activity haram, but some of it exists which punishes conditionally haram, makruh and even some who thinks it's permissible. This article will discuss each each opinion with a comparative perspective of schools of thought for then the assessment is carried out. From the author's assessment, it seems opinions that condemn masturbation are stronger and more realistic for applied.